Evaluation of the Achievement of 30% Women's Representation in the DPRD Purworejo Period 2024 - 2029 based on Law No. 7 of 2017 concerning Elections - Sapardiyono; Sobirin; Ahmad (Suara Edukasi Hukum, 2025)
This research examines women's representation in the Regional People's Representative Council (DPRD) of Purworejo Regency in the 2024 General Election (Pemilu), with a focus on the implementation of the minimum quota of 30% female legislative candidates based on applicable regulations. The research method used is empirical juridical, which is a combination of legal analysis of laws and regulations related to women's representation and empirical data collection through official statistics and interviews with members of the local Election Supervisory Agency (Bawaslu). The results show that although quota regulations have been administratively implemented, women's representation has only reached around 20%, still below the target mandated by Law No. 7/2017. Structural barriers such as the dominance of economic capital, political networks, as well as patriarchal cultural factors and gender stereotypes still limit women's broad participation. In addition, voter trust in female candidates is also a significant challenge. This research recommends regulatory reforms that not only regulate candidate quotas, but also affirmation mechanisms in determining elected candidates and strengthening women's political capacity. Changes in political culture that are inclusive and gender-friendly are also considered crucial to increase women's representation in a real and sustainable manner at the local level.